Periodontal condition in relation to nutritional status among kindergarten children in Al-Ramadi city/Iraq - Inaam M Suhail; Wesal Al-Obaidi (College of Dentistry/ University of Baghdad, 2014)
Background: Nutrition can affect periodontal disease through contributing to microbial growth in the gingival crevice, affecting the immunological response to bacterial antigens and assisting the repair mechanism of the connective tissue at the local site after injury from plaque and calculus. The aim of this study was to assess the prevalence of Oral hygiene (plaque and calculus) and gingivitis in relation to age, gender and nutritional status. Materials and methods: The sample included (444) kindergarten children at age of (4 and 5 years old) males and females from urban areas in Al-Ramadi city. The assessment of nutritional status was performed using anthropometric measurements (Waterlow's indicator). Plaque index of Silness and Loe (1964) used for plaque assessment, gingival index of Loe and Silness (1963) was used for recording gingival health condition. Ramfjord index teeth (1959) were applied to assess oral cleanliness and gingival condition. Results: The mean value of plaque, Gingival and Calculus indices were found (1.64±0.02, 0.38±0.02, 0.0004±0.0002 respectively). Plaque index and gingival index were reported to be higher among malnourished children than well nourished described by Waterlow´s indicator, with statistically highly significant differences. No significant difference was recorded in calculus index between the malnourished and well nourished children. Conclusions: There was a direct relationship between periodontal condition and malnutrition.